1982
DOI: 10.1523/jneurosci.02-09-01299.1982
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of retrograde axonal transport delays the onset of metabolic and morphologic changes induced by axotomy

Abstract: Axotomy-induced increase in 2-deoxyglucose (2-DG) uptake by motor nuclei and neuronal chromatolytic changes were studied after subepineural injection of colchicine into the motor nerve. Hypoglossal nuclei of either cats or rats were axotomized bilaterally, while one of the nerves was injected with colchicine or saline proximal to the site of nerve transection and the other was left intact or injected with saline. Colchicine abolished or decreased the uptake of 2-DG by axotomized nuclei and delayed the onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Other investigators have demonstrated vigorous axonal regrowth from different populations of neurons with diffusely-branched axons (Bj6rklund et al, 1979(Bj6rklund et al, , 1980Olson et al, 1983;Nornes et al, 1983;Gage et al, 1983;Aguayo et al, 1984). If regenerative axonal growth is signalled by an effect of injury that is relayed retrogradely to the neuronal perikaryon (Cragg, 1970;McQuarrie & Grafstein, 1973;Singer et al;Aguayo, 1985), injury to multiple axonaI branches might enhance the regenerative responses of neurons with branched axons, such as those of the RNT, by additive influences on the growth-regulating processes of neurons. Such an additive mechanism has been demonstrated for the bipolar dorsal root ganglion neurons in which the regrowth of severed central axons ~n the spinal cord is dramatically enhanced by transection of the peripheral axons of the same neurons .…”
Section: Axonal Branchingmentioning
confidence: 98%
“…Other investigators have demonstrated vigorous axonal regrowth from different populations of neurons with diffusely-branched axons (Bj6rklund et al, 1979(Bj6rklund et al, , 1980Olson et al, 1983;Nornes et al, 1983;Gage et al, 1983;Aguayo et al, 1984). If regenerative axonal growth is signalled by an effect of injury that is relayed retrogradely to the neuronal perikaryon (Cragg, 1970;McQuarrie & Grafstein, 1973;Singer et al;Aguayo, 1985), injury to multiple axonaI branches might enhance the regenerative responses of neurons with branched axons, such as those of the RNT, by additive influences on the growth-regulating processes of neurons. Such an additive mechanism has been demonstrated for the bipolar dorsal root ganglion neurons in which the regrowth of severed central axons ~n the spinal cord is dramatically enhanced by transection of the peripheral axons of the same neurons .…”
Section: Axonal Branchingmentioning
confidence: 98%
“…5a). Administration of colchicine, a drug which blocks axonal transport, significantly delays chromatolysis and RAG expression (Singer et al, 1982; Murphy et al, 1999). Proteomic analysis of these signaling complexes revealed a variety of proteins being trafficked including, JUN amino-terminal kinase (JNK), STAT3, dual leucine zipper kinase (DLK), and gp130 cytokines, among others (Michaelevski et al, 2010a).…”
Section: The Cell Body Response To Axotomymentioning
confidence: 99%
“…The profound alterations in retrograde transport reported herein are (Cragg, 1970;Kristensson and Sjostrand, 1972;Pilar and Landmesser, 1972;Grafstein, 1975;Bisby and Bulgar, 1977;Singer et al, 1982). Recent experiments by Singer et al (1982) have demonstrated that both metabolic and morphologic changes in the perikarya following axotomy may be delayed by administration of colchicine proximal to axotomy. These data suggest it is the appearance of a signal, rather than the lack of one, which is responsible for initiating at least some soma1 responses to axon damage.…”
Section: Nsmentioning
confidence: 49%
“…Administration of acrylamide, however, in doses equal to 50 mg/kg (0.65 mmol/kg) or less re-T'he specific role that altered retrograde transport may Serve in the etiology of acrylamide-induced ax-Onopathy has yet to be Jakobsen and Sidenius (1983) suggested that altered retrograde transport, in the presence of essentially normal fast anterograde transport (Bradley and williams, 1973;Sumner et al, 1976;Griffin and Price, 1976;Sidenius and Jakobsen, 1983), may be responsible for the accumulation of multivesicular bodies and tubuiovesicular structures in distal portions of axons from acrylamide-treated animals Griffin et al, 1977). The profound alterations in retrograde transport reported herein are (Cragg, 1970;Kristensson and Sjostrand, 1972;Pilar and Landmesser, 1972;Grafstein, 1975;Bisby and Bulgar, 1977;Singer et al, 1982). Recent experiments by Singer et al (1982) have demonstrated that both metabolic and morphologic changes in the perikarya following axotomy may be delayed by administration of colchicine proximal to axotomy.…”
Section: Nsmentioning
confidence: 71%